OSACS score-a new simple tool for identifying high risk for Obstructive Sleep Apnea Syndrome based on clinical parameters - Szymanski, Filip M. (Anatol J Cardiol, 2015)
OBJECTIVE: Obstructive sleep apnea syndrome (OSAS) is a cardiovascular risk factor associated with clinical complications like hypertension, ischaemic heart disease or thrombosis. The aim of this study was to develop a new scoring system, based on objective clinical and echocardiographic parameters. METHODS: One hundred fifty-eight consecutive acute coronary syndrome (ACS) patients underwent standard clinical, laboratory and echocardiography assessment after ACS, and their risk of OSAS was assessed using Berlin Questionnaire and Epworth Sleepiness Scale. Creation of OSACS (Obstructive Sleep Apnea in Acute Coronary Syndrome patients) score was attempted, with risk factors evaluated in multiple logistic regression model. RESULTS: In 34.2% patients, who were at high risk of OSAS left ventricular diastolic diameter, left atrial diameter, and intrventricular septal thickness were elevated. In multiple logistic regression analysis: history of hypertension (Odds Ratio 4.42; 95% CI 0.96-20.5, p=0.06), body mass index (OR 6.82; 95% CI 2.33-20; p<0.001), diastolic blood pressure (OR 6.4; 95% CI 1.58-25.9; p=0.01), left ventricular diastolic diameter (OR 3.5; 95% CI 1.05-11.6; p=0.04), left ventricular mass index (OR 0.26; 95% CI 0.07-0.94; p=0.04), interventricular septal thickness (OR 4.44; 95% CI 1.15-17.1; p=0.03) were independent risk factors for high risk of OSAS. All independent risk factor were implemented into risk prediction model called OSACS. The area under the ROC curve for the OSACS score was 0.87. CONCLUSION: OSAS is highly prevalent in ACS patients. The new OSACS score has a high predictive value in assessment of risk of OSAS in these patients, and it can be used as an objective tool, and an alternative for the Berlin Questionnaire.